A strategy to conserve agricultural water use in Colorado's Front Range - Varzi, Manijeh Mahmoudzadeh, author; Oad, Ramchand, author; Colorado State University, publisher (Colorado State University. Libraries, 2015)
For the joint sustainability of agriculture and other economic sectors, agriculture water use will need to become more efficient and productive in the future. And, indeed, there are opportunities in the agriculture sector for water conservation by utilizing modern technology such as the drip irrigation and the practice of deficit irrigation. A collaborative research effort will be undertaken by the United Water and Sanitation District, the Platte River Water Development Authority, the 70 Ranch, Netafim, and the Colorado State University. The overall goal of the collaborative research is to generate knowledge for preserving the strong agricultural economy of the South Platte Valley in Eastern Colorado, while at the same time freeing up some water for other societal needs. This will be done by establishing a research/extension station in the region and conducting experimentation on more efficient irrigation technologies such as subsurface drip irrigation and deficit irrigation. The underlying premise is that by following such crop and water management practices, the farmers can increase their net economic returns. The planning horizon to achieve this long-term goal is about 15-20 years, but some practical answers to specific research questions should be available in early phases. This document briefly discusses a research proposal focused on the initial stage of the above study (first two years). The aim is to examine: (a) the feasibility of drip irrigation and (b) the effect of deficit irrigation on some of the drought resistant local crops in order to define the feasibility of deficit irrigation for farmers. Field work and data collection starts on summer 2015.
Hydrology days 2015
AGU hydrology days 2015
2015 annual AGU hydrology days was held at Colorado State University on March 23 - March 25, 2015.